Tracking nanoscopic particles with interferometer scattering microscopy - Wong, Kuan Hua (Nanyang Technological University, 2023)
The characterization of particles is crucial in the biomedical research field and can be accomplished using a variety of imaging modalities and detection methods. Single particle tracking (SPT) is a technique that enables the study of nanoscale objects' trajectories, but its fluorescence-based implementation has limited spatiotemporal resolution due to various factors. On the other hand, interferometric scattering (iSCAT) microscopy is a non-fluorescent interference-based imaging technique that can achieve highly sensitive detection of nanoscale objects and investigate their dynamics at the nanoscale level. SPT based on iSCAT provides high spatiotemporal resolution, with limitations only imposed by the intrinsic properties of the detection system and shot noise.